Sustainable Entrepreneurship: Romanian Entrepreneurs’ Funding Sources in the Present-Day Context of Sustainability - Anton Carmen Elena; Zamfirache Alexandra; Albu Ruxandra-Gabriela; Suciu Titus; Sofian Sergiu Mihai; Ghiță-Pîrnuță Oana-Andreea (Sustainability, 2024)
This paper aims to provide an in-depth analysis of the knowledge of and access to funding sources in the context of sustainability. Additionally, it seeks to analyse the perspectives and intentions of entrepreneurs regarding the use of such sources in the future. For this purpose, quantitative research was conducted, and data were collected from a sample of 267 respondents, companies operating in the Central Region of Romania. The evidence indicates that reinvestment of profits is the most commonly used funding source, followed by bank loans and leasing. The least-used and least-known funding source are Business Angels. Among the conclusions of the study, the demonstration of the link between the level of use of the funding sources, which moderates the close relationship between sustainability and the financial performance of a company, is noteworthy. Ultimately, this research opens new ways for collaboration between the academic environment, government, and local authorities. The results can be beneficial for stakeholders at both the micro- and macroeconomic levels interested in the sustainable development of the SME sector.
This article was originally published in Sustainability (MDPI) and is licensed under a Creative Commons Attribution (CC BY) 4.0 International License. This license permits use, sharing, distribution, and reproduction in any medium or format, provided appropriate credit is given to the original authors and source, a link to the license is included, and any changes are indicated. The article is available at: https://www.mdpi.com/2071-1050/16/2/654 To view a copy of this license, visit: http://creativecommons.org/licenses/by/4.0/